The use of Remdesivir in pregnant women with COVID-19 - Gulbanu Shaimerdenova; Gulzhan Abuova; Gaziza Yelshibek; Aisholpan Zhuparbek; Gulzhanat Bakytzhan; Samal Ashtayeva; Laura Sarypbekova (National Scientific Medical Center, 2023)
Objectives: This study was conducted to investigate the use of Remdesivir among pregnant women with probable and confirmed Covid-19 coronavirus infection. Material and methods: To implement the study, a comprehensive examination of 120 pregnant women with severe and extremely severe forms of coronavirus infection was conducted. Results: Statistically significant differences were obtained (p=0.019) at the time of comparison between the main and control groups, depending on the age of the subjects. The studied differences are due to the higher frequency of the age group 33-42 years among patients taking Remdesivir compared to those who were in the control group (p = 0.036). Women of the main group (Me = 9.00; Q1-Q3 = 8.00-11.0) stayed longer in the hospital compared to women in the control group (Me = 8.00; Q1-Q3 = 7.00-10.0). The more severe condition of patients in this group is cause of that. There are statistically significant differences in changes in amniotic fluid according to ultrasound data in the control and main groups (p=0.013). According to the results of our study, it was found that the decrease in temperature to a normal level occurred earlier in the control group (68%) than in the main group. Conclusion: The older age group and the third trimester of pregnancy are risk factors for the transition to a severe form of the disease. Reliable efficacy of the etiotropic drug Remdesivir could not be traced.